Hubungan Peran Kader Dengan Kelengkapan Imunisasi Dasar Pada Bayi Usia 9 – 12 Bulan Di Posyandu Desa Wakasihu - Yerry Soumokil; Suryanti Tukiman; Hindun Makatita (Jurnal Ilmu Kesehatan dan Gizi, 2024)
The community's participation in various health development efforts can be seen, among other things, from Community Resource Health Efforts (UKBM) which are growing rapidly in the form of (Posyandu), (POD) and Health Funds. This study aims to determine the relationship between the role of cadres and the completeness of basic immunizations for babies aged 9 - 12 months at the Posyandu in Wakasihu Village. This type of research is non-experimental quantitative research with an analytical survey method, a cross sectional study approach. This research was conducted in Wakasihu village. A sample of 87 mothers of babies was taken using a total sampling technique. The research instruments were questionnaires and observation sheets, and the research results were analyzed using the chi-squer test. Most of the cadres' role in providing services is not good, namely 31 people (35.6%), most of the basic immunization requirements for babies aged 9 - 12 months at posyandu have not received complete immunization, 29 people (33.3%). The chisquere test results were obtained with a p value of 0.048. This means that H0 is rejected and Ha is accepted where there is a relationship between the role of cadres and the completeness of basic immunization for babies aged 9 - 12 months at the posyandu in Wakasihu Village. From the results obtained, the majority of mothers who have babies in Wakasihu village do not want to take their children to the posyandu because according to them the role of cadres is lacking, so for future researchers, please look again at the role of cadres during the posyandu.